Milk product safety and household food hygiene influence bacterial contamination of infant food in peri-urban Kenya - Hoffmann, Vivian; Simiyu, S.; Sewell, D.K.; Tsai, K.; Cumming, O.; Mumma, J.; Baker, K.K. (Frontiers Media, 2022)
Background: Milk is a common infant food in peri-urban Kenya that can transmit diarrhea-causing enteric pathogens. Little is known about how contamination of milk at point of purchase and household handling of milk-based infant foods contribute to infant exposure to enteric pathogens.